Analysis of the Factors Affecting Infant Birth Weight in a Neonatal Care Unit in RSD Dr. Soebandi Jember - Utami, Resti; Ernawati; Rahayuningtyas, Yayuk; Santy, Wesiana Heris; Hidaayah, Nur; Yulis, Zuhrotul Eka (International Journal of Psychosocial Rehabilitation, 2020)
Infant birth weight is an important indicator of a child’s vulnerability to the risk of illness in childhood. Infant birth weight is very closely related to the health and survival of newborns. Low birth weight (LBW) is a major cause of death in newborns. Therefore the identification of the factors that contribute to infant birth weight is very important to be able to reduce the risk factors and promote care in all stages of pregnancy. The purpose of this study was to explore the factors that influence infant birth weight in a neonatal care unit. This study used an observational analysis with a cross-sectional approach. The sample consisted of 92 respondents. The sampling technique used was simple random sampling. The variables in this study were antenatal care (ANC) history, complications in the pregnancy, birth method and infant birth weight. The data was collected using a structured questionnaire and analyzed using logistic regression. The results showed that (1) history of antenatal care (ANC) ≥ 4 times (OR 3,4) and complications in the pregnancy (OR 4.0) have a significant effect on the infant’s birth weight and (2) the birth method has no significant effect concerning the infant’s birth weight. The antenatal care (ANC) history factors and complications in the pregnancy are logically adequate at explaining the affect o an infant’s birth weight in the neonatal care unit. Health workers are expected to be able to apply an infant birth weight prediction model to provide early warnings about situations where there are difficulties or complications. They should conduct immediate management with appropriate therapy to anticipate the LBW events that will occur.